Design of a secure file storage and access protocol for cloud-enabled Internet of Things environment. (September 2021) - Karati, Arijit; Amin, Ruhul; Mohit, Prerna; Sureshkumar, Venkatasamy; Biswas, G.P.
Abstract: The so-called cloud-enabled Internet of Things (CIoT) systems interconnect numerous devices to render robust data storage, efficient analysis, and message exchange features. However, it confronts the confidentiality of data from the owner as the access control of data is performed by honest-but-curious service providers. Although the encryption strategy ensures data security, it has adverse data deliverance due to its inherent all-or-nothing decryption. Thus, a robust protocol is proposed to achieve data sharing among geographically dispersed physical devices and efficient access to cloud data for clients. The proposed protocol resists the chosen-ciphertext attack (CCA) based on the hardness of the Decisional Diffie–Hellman Inversion (DDHI) assumption. The comprehensive analysis and simulation results show that our protocol is efficient in computation, communication, and storage costs.